Integrative Approaches for Health : Biomedical Research, Ayurveda and Yoga - Patwardhan, Bhushan; Mutalik, Gururaj; Tillu, Girish (London : Academic Press, 2015)
Despite spectacular advances, modern medicine faces formidable global challenges in several key areas-notably the persistence of major killer diseases such as malaria, tuberculosis, leprosy, and newer threats including HIV/AIDS, resistant infections, and Ebola. As such, modern medicine has not led to a significant decrease in chronic diseases like diabetes, obesity, and other degenerative and autoimmune diseases. The authors believe that modern medicine needs to experience a paradigm shift, an integration of traditions-in particular from the ancient systems like Ayurveda and Yoga. Integrative Approaches for Health: Biomedical Research, Ayurveda and Yoga brings together the basic principles of interdisciplinary systems approach for an evolving construct of future medicine. Such an approach is already emerging at the cutting edge of current research in omics, bioinformatics, computational and systems biology. Several leading institutions of medicine have adopted Yoga and complementary medicine to widen their reach, and deepen effectiveness in therapeutic practices. The amalgam of modern medicine, with its strengths in scientific rigor, blended with the basic principles of life drawn from Ayurveda and Yoga might evolve into a medicine of tomorrow. Integrative approaches are no longer alternative, perhaps taking these approaches is the only possible way to heal our sick planet. This book introduces important trends and tools for biomedical researchers and physicians alike, to innovate the practice of medicine for the better.
Chapter 9 -- Drug Discovery and Ayurveda.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Integrative medicine; Medicine -- Research; Medicine, Ayurvedic; Yoga; Integrative Medicine; Evidence-Based Medicine; Medicine, Ayurvedic; Yoga; Integrative medicine; Medicine -- Research; Medicine, Ayurvedic; Yoga; MEDICAL -- Pharmacology; Integrative medicine; Medicine, Ayurvedic; Medicine -- Research; Yoga; Electronic books